Perancangan Detektor Kebocoran Gas LPG Berbasis Arduino yang Terhubung dengan Smartphone - Ade Mutaqin; Erwin Sitompul (President University, 2021)
LPG (Liquefied Petroleum Gas) has become the fuel for cooking for most households in Indonesia. The use of LPG for cooking requires high level of caution, due to the danger that may arise from gas leakage. If the molecules of flammable LPG gas are present in the air at a certain concentration and there is a triggerring factor in the form of flame or sparks, explosion and fire may occur. To prevent disasters caused by a LPG gas leakage, the author proposed an Arduino-based LPG gas leak detector (GLD). The GLD is equipped with a MQ-2 gas sensor, capable of measuring the LPG concentration in air in units of parts per million (ppm). Based on the measurement result, the GLD provides an early warning of LPG leakage through 3 condition levels: Normal, Alert, and Danger. Each condition level is characterized by the activation of LED indicators, a miniature air circulation fan , and a buzzer. Alert warning is released when the sensor reads more than 400 ppm (2.05% of LPG Lower Explosive Level). Danger warning is given at 800 ppm (4.10% of LPG Lower Explosive Level) or higher reading. An HC-06 Bluetooth module creates a wireless connection between the GLD and a smartphone. Through an application created on Blynk platform, the smartphone can monitor the LPG concentration at a distance of 10 m from the GLD. The GLD is tested and succeeded to detect gases coming from an LPG cylinder and from a gas lighter. The GLD also runs perfectly for the designed early warning scheme.